2016
DOI: 10.1093/nar/gkw533
|View full text |Cite
|
Sign up to set email alerts
|

Splice-switching antisense oligonucleotides as therapeutic drugs

Abstract: Splice-switching oligonucleotides (SSOs) are short, synthetic, antisense, modified nucleic acids that base-pair with a pre-mRNA and disrupt the normal splicing repertoire of the transcript by blocking the RNA–RNA base-pairing or protein–RNA binding interactions that occur between components of the splicing machinery and the pre-mRNA. Splicing of pre-mRNA is required for the proper expression of the vast majority of protein-coding genes, and thus, targeting the process offers a means to manipulate protein produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
321
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 416 publications
(328 citation statements)
references
References 168 publications
1
321
0
6
Order By: Relevance
“…Exon splice-modulating therapy has arrived in the clinic with the recent approval of AONs for the treatment of DMD and SMA (24,39). The field of RNA-targeting therapeutics continues to expand with new splice-switching oligonucleotide therapies designed to treat multiple disorders (40). In the current study, we evaluated an AON-mediated exon-skipping strategy to treat LGMD 2C.…”
Section: Discussionmentioning
confidence: 99%
“…Exon splice-modulating therapy has arrived in the clinic with the recent approval of AONs for the treatment of DMD and SMA (24,39). The field of RNA-targeting therapeutics continues to expand with new splice-switching oligonucleotide therapies designed to treat multiple disorders (40). In the current study, we evaluated an AON-mediated exon-skipping strategy to treat LGMD 2C.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, AOs are being used to treat various muscular and neurodegenerative diseases at varying stages of clinical trials, as well as a variety of other disease such as cancer [205]. A recent review showed that over 25 genes have been targeted using splice-switching AOs.…”
Section: Suppression/modification Of Mutant Gene Expression and Protementioning
confidence: 99%
“…A recent review showed that over 25 genes have been targeted using splice-switching AOs. These AOs are used as therapeutics to redirect pre-mRNA splicing, in which sequences vital to pre-mRNA processing are targeted, effectively blocking binding of the splicing factors to the region [205,206]. These types of AOs can be used to restore gene function, correct aberrant splicing, produce a novel transcript or even down regulate gene expression [205].…”
Section: Suppression/modification Of Mutant Gene Expression and Protementioning
confidence: 99%
See 1 more Smart Citation
“…These numbers combined with the number of known splicing mutations indicate that up to one-third of all disease-causing mutations might change pre-mRNA splicing (27,28). It has been shown that using an ASO-based approach one can manipulate the outcome of splicing, so that a particular exon can be selectively removed or included (29,30). Therefore, ASOs represent an invaluable tool that could be used for therapeutic purposes to treat a human disease caused by aberrant splicing.…”
Section: Introductionmentioning
confidence: 99%